Lecocytes mutation load declines with age in carriers of the m.3243A>G mutation: A 10‐year Prospective Cohort. Issue 4 (14th March 2018) - Langdahl, J.H.; Larsen, M.; Frost, M.; Andersen, P.H.; Yderstræde, K.B.; Vissing, J.; Dunø, M.; Thomassen, M.; Frederiksen, A.L.
Abstract : Carriers of the mitochondrial mutation m.3243A>G presents highly variable phenotypes including mitochondrial encephalomyopathy, lactoacidosis and stroke‐like episodes (MELAS). We conducted a follow‐up study to evaluate changes in leucocyte heteroplasmy and the clinical phenotypes in m.3243A>G carriers. Leucocyte heteroplasmy was determined by next generation sequencing covered by 100 000X reads in 32 individuals with a median follow‐up of 10.2 years. Ten‐year clinical follow‐up is reported in 46 individuals. The annual leucocyte mutation level declined by −0.7 (±0.4) percentage points/year ( P < .0001), and correlated with the level of the initial sample ( ρ = −0.92, P < .0001). Eleven of 46 m.3243A>G carriers died and clinical symptoms progressed. This longitudinal study shows the decline in leucocyte m.3243A>G heteroplasmy associates with the level of the initial sample. Further, there was a high mortality among carriers. Abstract :